2021
DOI: 10.1088/1361-6528/abe577
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of biosynthesized silver nanoparticles, amoxicillin, and glass-ionomer cement against Streptococcus mutans and Staphylococcus aureus

Abstract: Background. The development of dental caries is associated with various microorganisms and secondary caries formation is the main cause of restorations failure. The advice for restorative dental materials that have antimicrobial properties has stimulated the introduction of materials containing different antibacterial agents. Objectives. The present study has been designed to synthesize silver nanoparticles (AgNPs) and incorporate AgNPs and amoxicillin into glass ionomer cement (GIC) to synergize its effect on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 48 publications
6
27
0
Order By: Relevance
“… 44 As for AMP@PDA@AgNPs, the apparent absorption peak at 412 nm originated from the conjugation of AgNPs. 51 The study by Enas et al 24 showed an absorption maximum at 429 under the cupressus macrocarpa extract biosynthesis of AgNPs. Slight variation in absorption peak may be attributed to difference in the amount of the reducing chemicals present in the extracts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 44 As for AMP@PDA@AgNPs, the apparent absorption peak at 412 nm originated from the conjugation of AgNPs. 51 The study by Enas et al 24 showed an absorption maximum at 429 under the cupressus macrocarpa extract biosynthesis of AgNPs. Slight variation in absorption peak may be attributed to difference in the amount of the reducing chemicals present in the extracts.…”
Section: Resultsmentioning
confidence: 99%
“…To settle this problem, different methods have been used to modify AgNPs. [24][25][26] For instance, Ramyaa et al reported that dexamethasone-silver nanoparticles embedded in dendritic collagen matrix nanoparticles reduced biofilm formation in Staphylococcus aureus and Klebsiella pneumonia. 26 With the rapid development of nanotechnology, a lot of novel antimicrobial agents and methods have been put forward and studied, such as antibacterial peptides (AMP), 27,28 quaternary ammonium compounds, 29 quantum dots, 30 photodynamic therapy 31 and photothermal therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oil from cactus pear seed has been found to have an appreciable amount of oil with high levels of unsaturated fatty acids, with antioxidant and antimicrobial activity as well as cardioprotective, antithrombotic, antiinflammatory, antiarrhythmic, hypolipidemic, and antihyperglycemic effect [8,9]. Dental caries is a disease caused by the interactions between bacteria, foods, and saliva within the dental plaque and its major causative germ is known as S. mutans, among the germs present in the dental plaques [10]. S.mutans, as gram-positive and facultative anaerobic bacteria, generates acid and acidifies the environment within the dental plaque since it is acid-resistant.…”
Section: Introductionmentioning
confidence: 99%
“…S.mutans were found within the human mouth and is to blame for inflicting dental tooth decay [9]. Once dental biofilm remains on the tooth surface with sugars and bacterium, the sugars are converted into organic acid by metabolism [10].…”
Section: Introductionmentioning
confidence: 99%